2006
DOI: 10.1002/bies.20512
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the nucleophosmin/nucleoplasmin family of nuclear chaperones

Abstract: Basic proteins and nucleic acids are assembled into complexes in a reaction that must be facilitated by nuclear chaperones in order to prevent protein aggregation and formation of non-specific nucleoprotein complexes. The nucleophosmin/nucleoplasmin (NPM) family of chaperones [NPM1 (nucleophosmin), NPM2 (nucleoplasmin) and NPM3] have diverse functions in the cell and are ubiquitously represented throughout the animal kingdom. The importance of this family in cellular processes such as chromatin remodeling, gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
170
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(177 citation statements)
references
References 90 publications
(145 reference statements)
3
170
0
4
Order By: Relevance
“…B23 Regulates GCN5-mediated Histone Acetylation-Both B23 and GCN5 are involved in histone post-translational regulation (1,17). B23 can bind histones functioning as a histone chaperone and promote nucleosomal assembly in vitro (17), whereas recombinant full-length mammalian GCN5 is competent for the acetylation of nucleosomal histones (27).…”
Section: Identification Of Gcn5 As a B23-interacting Protein Inmentioning
confidence: 99%
See 2 more Smart Citations
“…B23 Regulates GCN5-mediated Histone Acetylation-Both B23 and GCN5 are involved in histone post-translational regulation (1,17). B23 can bind histones functioning as a histone chaperone and promote nucleosomal assembly in vitro (17), whereas recombinant full-length mammalian GCN5 is competent for the acetylation of nucleosomal histones (27).…”
Section: Identification Of Gcn5 As a B23-interacting Protein Inmentioning
confidence: 99%
“…B23 can bind histones functioning as a histone chaperone and promote nucleosomal assembly in vitro (17), whereas recombinant full-length mammalian GCN5 is competent for the acetylation of nucleosomal histones (27). In order to scrutinize the biological and biochemical significance of the The immunoprecipitates were then separated by SDS-PAGE and probed with anti-B23 or GCN5 antibodies.…”
Section: Identification Of Gcn5 As a B23-interacting Protein Inmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been recently shown that oncogene-induced senescence is associated with signs of DNA replication stress (Di Micco et al, 2006). Considering that wild-type NPM has a function in modulating chromosome condensation/decondensation and is recruited to sites of dsDNA breaks (Frehlick et al, 2007), we hypothesized that NPMc þ may lead to senescence by blocking the NPM function in DNA damage response. However, at the passage where senescence and growth curve was analysed, overexpression of NPMc þ in wildtype MEFs was not accompanied by positivity for markers characteristically induced in cells suffering DNA damage as shown by the scarce nuclear staining NPMc + is an oncogene K Cheng et al of phospho-histone H2A.X (Ser139), unlike those of the UV-irradiated MEFs (Supplementary Figure 3A).…”
Section: E1a Rescues Npmc þ -Induced Senescencementioning
confidence: 99%
“…They can be further classified into four groups, based on sequence similarities: NPM1 (nucleophosmin), NPM2 (nucleoplasmin), NPM3, and NPM-like invertebrate proteins. 11 The hallmark of all family members is the presence of a well-conserved N-terminal core domain that, following a short methionine-rich unstructured sequence of unknown function, extends for 100 residues ( Fig. 1) and folds as a eight-stranded beta-barrel, composed of two opposing antiparallel fourstranded sheets.…”
Section: Introductionmentioning
confidence: 99%